(untitled) (Global Journal of Human-Social Science, 2018)
The aim of the paper were to present the patterns and cultural identities on Pra-guam silver beads and conceptual design silk patterns based on cultural identities of Khmer people in Surin province of Thailand.The qualitative methods were used in the study were data collection by in-depth-interview and observationacademic papers.The results of the paper are the patterns on Pra-guam silver beads consist of 5 ancient patterns such as 1) Lotusflower2)Ma-Yom Seed3) Phigool Flower4) Hae 5) Jarl.The concept of cultural design of silk patterns based on the cultural identities preservation is that the design must to represented the cultural identities (B = belief M=meaning D=doctrine V=value)the new pattern on the silk name are Lotusflower 2) Ma yom seed3) Phigool Flower4) Hae5) Jarl.